If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6b + 5 + 4b = -3b + 10 Reorder the terms: 5 + -6b + 4b = -3b + 10 Combine like terms: -6b + 4b = -2b 5 + -2b = -3b + 10 Reorder the terms: 5 + -2b = 10 + -3b Solving 5 + -2b = 10 + -3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '3b' to each side of the equation. 5 + -2b + 3b = 10 + -3b + 3b Combine like terms: -2b + 3b = 1b 5 + 1b = 10 + -3b + 3b Combine like terms: -3b + 3b = 0 5 + 1b = 10 + 0 5 + 1b = 10 Add '-5' to each side of the equation. 5 + -5 + 1b = 10 + -5 Combine like terms: 5 + -5 = 0 0 + 1b = 10 + -5 1b = 10 + -5 Combine like terms: 10 + -5 = 5 1b = 5 Divide each side by '1'. b = 5 Simplifying b = 5
| 2x^2+x+1=-0 | | 0.12(24)+0.02x=0.06(12+x) | | 0.30x+0.05(20-x)=0.10(-35) | | x^4+7x^2+16= | | 3x^2+x-42=0 | | 0.7y-0.3y=6.4 | | 2x^3-15x^2-84x+5=0 | | A+b=w-2 | | 3y=88-2x | | 4+3x-1=9x+11-5x | | 0.16(24)+0.04x=0.08(18+x) | | -(6x+3)-(8x-7)=8-(5x+1) | | 6m-8=2+9m-6 | | 10-4x=-2+8x | | 2x+13=37 | | 3t=1 | | 4y-12=-3y | | [x]-y=2 | | 3t=-1 | | 4x+43x+30x=0 | | 2y=1-xy | | 1-0x=0 | | .14y+6=-19 | | 3x-2x=6 | | 15+k=-9 | | b+2b+(b+15)=95 | | 6=13+q | | 11z=-33 | | 6(-4)= | | 8*-7= | | (x^2)=-4 | | y+23=-1 |